Mapping the clinical trial landscape of multiple primary lung cancer in the era of precision oncology: persistent exclusion and design limitations hamper evidence-based treatment development - Shi, Jianwei; Liang, Linchuan; Gao, Yushun (Frontiers in Oncology, 2025)
Multiple primary lung cancer (MPLC) is increasingly recognized for its clinical and biological significance, yet it remains strikingly underrepresented in clinical trials. We systematically analyzed 8,212 lung cancer trials registered between 2015 and 2024 across four major international registries, finding that only 18 (0.22%) explicitly included MPLC patients. Most of these trials were early-phase, observational, and surgery-focused, with minimal incorporation of biomarker-driven or precision strategies. This underrepresentation reflects a structural exclusion rooted in traditional single-lesion trial paradigms. It is further exacerbated by limited engagement from industry and government sponsors due to high trial complexity and low commercial incentive. Inclusion-oriented frameworks are urgently needed to align research with MPLC’s clinical reality.